Peran Kualitas Jasa dan Kepuasan Nasabah Terhadap Kesetiaan Nasabah Serta Minat Untuk Berpindah Bank - Catharina Clara (Prosiding University Research Colloquium, 2018)
With so many banks in the banking system in Indonesia then certainlycompetition between banks is getting fierce. Each bank must inevitably createa superior quality of service compared to competitors so as to satisfycustomers who ultimately result in customer loyalty or intention to switchbanks considering the cost of bank switching (switching cost) is low. On theother hand banks must also comply with the guidelines of Bank Indonesia andthe Financial Services Authority (FSA/ OJK). Based on this phenomenon thenexamined whether the perceived quality of the customer in this case is relatedto the bank customer satisfaction and loyalty as well as affect the desire orinterest to switch banks. So the research problems are: 1) How does thequality of services and customer satisfaction bank and 2) What is the impactof customer satisfaction to customer loyalty and switch intention. Thisresearch is a survey conducted in Palembang to the people who are customersof banks in Palembang. Linear regression model used to measure therelationship between variables. To answer the first question, the independentvariables of service quality (with 3 sub-variables: customer expectation,perceived quality, perceived value) regressed multiple with customersatisfaction. Meanwhile, to answer the second question, simple regressionused to measure effect of customer satisfaction with customer loyalty andswitch intention. The test results show that the reliability and validity ofresearch instrument is already showing good reliability and validity. Similarlyresult with the classical assumption test. The influence of the quality ofservices measured using subvariable Customer Expectation, PerceivedQuality and Perceived Value, to the customer satisfaction showed significancefor the variable Perceived Quality. Customer satisfaction on customer loyaltysignificantly positive effect. Customer satisfaction against switch intentionalso significant but positive influence. Overall, these models haven‟t predictthe dependent variable properly.